Transforming Nigeria’s agrifood system: Wealthier, but also healthier - Ecker, Olivier; Brown, Tracy; Andam, Kwaw S. (International Food Policy Research Institute, 2021)
Malnutrition, largely attributable to poor diets among both the rich and poor, presents a growing challenge in Nigeria. This brief considers the obstacles to food security and better nutrition, particularly the country’s macroeconomic instability, widespread poverty, and the need for greater investment and coherence to support dietary diversity. The authors describe how a shift to focus on consumer needs can transform the agrifood system to deliver healthier and more affordable diets for all Nigerians, as well as better and more secure rural livelihoods.